Matthew Haysom, Maria Mili, and Jenny Wallensten (eds) The stuff of the gods. The material aspects of religion in ancient Greece. Skrifter utgivna av Svenska institutet i Athen, 4°, 59. - Santini, Marco (Journal of Greek Archaeology, 2025)
The volume under review originates from an international conference held on 7–9 July 2015 and organised by the Swedish Institute at Athens in collaboration with the British School at Athens. Despite the quite long time elapsed from the conference to the publication of the proceedings, the seventeen papers collected in the volume, preceded by an Introduction by the editors, duly take into account literature appeared since and are therefore up-to-date. The intellectual premises of the conference and volume are those of the material turn in the humanities and social sciences. The papers seek to apply its methodologies and research questions to the realm of Greek religion.